Legal Certainty of the Cash On Delivery System in electronic transactions in Indonesia - Kurniasih, Esy; Febrianti, Lidia; Octaviani Pratama, Marnisya; Dwi Milandry, Anggraini (International Conference On Law And Social Sciences, 2024)
COD is a payment method that is made directly on the spot after the order from the courier is received by the buyer. Electronic transactions using the Cash On Delivery (COD) payment method play an important role in increasing the intensity of electronic transactions in Indonesia because the COD payment method can reach consumers who do not have a bank account or consumers who are still unsure about the marker place they visit. The increasing number of people using the COD payment method is not in line with the public's perception of understanding the COD payment method, resulting in new problems such as consumers being reluctant to pay for goods they have ordered and protests accompanied by threats to delivery couriers. This article aims to examine the shortcomings in COD transactions in order to increase legal certainty for all parties in E-commerce transactions using the COD method. The type of research used by the author is normative legal research. Normative legal research is library legal research, because it uses library materials as the main basis for conducting this research. In normative legal research there are criteria for the type of research, namely research that discusses legal principles, legal systematics, level of legal synchronization, legal history. The nature of writing this paper is descriptive, namely the method used to explore and clarify a phenomenon or social reality by describing a number of variables relating to the problem or unit being studied. The analytical method used in this writing is descriptive qualitative, namely by discussing and analyzing the legal material obtained which is related to the focus being researched and presented in descriptive form. Legal material is analyzed using a qualitative descriptive method, namely describing a situation of an event obtained from research and then adjusting it to laws or regulations that are related to the focus of the writing. There are several shortcomings in this COD method, such as: Misunderstanding of the COD system, information provided by the seller is still different from the actual situation, and the method of purchasing goods is complicated. So this has an impact on couriers who experience quite a lot of problems compared to normal deliveries. The shortcomings of the COD system can be overcome by strengthening legal certainty. If the regulatory certainty is clear, it will guarantee that parties in ECommerce transactions using the COD method can carry out behavior in accordance with the provisions of the applicable law